Interdisciplinary Synthesis in Architecture: A Comparative Study of Technological Innovation and Cultural Agency - Das, Tapashi K.; Dutta, Kishore (International Journal of Architectural Engineering Technology, 2025)
In the evolving landscape of modern and contemporary architecture, the convergence of art, science, and technology has redefined traditional paradigms, challenged perceptions of space, and pushed the boundaries of structural innovation. This paper investigates how influential architects have integrated technological and material innovations to reshape both the practice and societal role of architecture. Adopting a comparative case study methodology, it examines the works of selected architectural masters whose approaches exemplify distinct modes of interdisciplinary engagement across art, technology, and culture. The analysis identifies three recurring features: the reconfiguration of authorship through collaboration, the emergence of novel spatial typologies enabled by digital design and advanced materials, and the repositioning of architecture as a mediator of societal and cultural change. By synthesizing these findings, the study advances a framework arguing that interdisciplinary design practices are not only transforming architectural production but also reshaping its broader cultural agency.